TikTok Users' Perception of Natasha Surya's Personal Branding on Social Media - Ratti, Kara Thania; Hariyanto, Didik (Procedia of Social Sciences and Humanities, 2024)
This study aims to find out the perception of Tiktok users towards Natasha Surya's personal branding on TikTok social media. This study uses a descriptive qualitative method to find data related to audience perception in seeing the success rate of Natasha Surya's personal branding and emphasizes more on the theory used to reach the conclusion stage, data collection through primary interviews with Whatsapp media and the content of Natasha Surya's account on TikTok. Data mining was carried out by means of open interviews. This study refers to Bernard Barelson's Theory of Perception in researching the perception of Natasha's personal branding. The results of the analysis show that Natasha Surya has succeeded in building a strong and effective personal branding perception on Tiktok through aesthetic, relevant, and inspiring visuals.